Incident osteoarthritis associated with increased allied health services use in ‘baby boomer’ Australian women - Parkinson, L.; Moorin, Rachael; Peeters, G.; Byles, J.; Blyth, F.; Caughey, G.; Cunich, M.; Magin, P.; March, L.; Pond, D. (Wiley-Blackwell Publishing Asia, 2016)
Objective: To explore impact of incident osteoarthritis (OA) on health services use by Australian women born 1946–51. Methods: Secondary analysis of Australian Longitudinal Study on Women's Health survey data linked to Medicare Australia databases (2002 to 2011). Medicare services use was compared for two groups: OA group (n=761) – reported incident OA in 2007; Never group (n=4346) – did not report arthritis in time frame. Interrupted time series regression compared health services use over time. Results: The OA group had higher health services use than the Never group. Rate of services use increased over time for both groups. Rate of increase in quarterly doctor attendances was significantly lower for the OA group after onset of OA, with no corresponding change for the Never group. Conclusions: A pre-existing higher use of health services is associated with reporting incident OA, compared to those who never report arthritis. After onset of OA, rate of doctor use reduced and allied health use increased, consistent with recommended Australian treatment guidelines. Implications: This study provides a rare insight into change in healthcare use for people reporting incident OA, against an appropriate comparison group, highlighting the importance of early diagnosis of OA to optimise effective use of health services.